Clima familiar y autoestima en estudiantes de cinco años de la Institución Educativa Inicial N° 259 Gotitas de Amor, Nauta 2024 - Vargas Dosantos, Karen Raquel (2025)
This study examines the relationship between family climate and self-esteem in 5-year-old preschool students. A quantitative approach with a non experimental, correlational design was used. The study analyzed data from 51 students, which represented 100% of the total population. The technique used was the survey, and the data collection instruments were structured questionnaires with specific questions. The results show a statistically significant relationship between family climate and self-esteem. The correlation coefficient (Rho = 0.741) indicates a positive and high correlation between both variables, suggesting that a favorable family climate is associated with higher self-esteem. An interesting result is that no statistically significant relationship was found between the family relationships dimension of family climate and self-esteem in 5-year-old students, suggesting that other family climate factors could have a greater impact on the self-esteem of these students. It is concluded that strengthening the family environment is a key factor in promoting self-esteem in children in early childhood education.